2022
DOI: 10.1186/s13075-022-02817-7
|View full text |Cite
|
Sign up to set email alerts
|

Semaphorin 3G exacerbates joint inflammation through the accumulation and proliferation of macrophages in the synovium

Abstract: Objectives Methotrexate (MTX) is an anchor drug for the treatment of rheumatoid arthritis (RA). However, the precise mechanisms by which MTX stalls RA progression and alleviates the ensuing disease effects remain unknown. The aim of the present study was to identify novel therapeutic target molecules, the expression patterns of which are affected by MTX in patients with RA. Methods CD4+ T cells from 28 treatment-naïve patients with RA before and 3 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…At present, studies have confirmed that ALPK1 is a promoting factor in several inflammation‐related diseases 11,12 . Meanwhile, M1 macrophage polarization plays an important role in the development of joint inflammation 37 . Moreover, M1 macrophages play a more critical role in cartilage damage in TMJOA patients than other common cell populations 38 .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…At present, studies have confirmed that ALPK1 is a promoting factor in several inflammation‐related diseases 11,12 . Meanwhile, M1 macrophage polarization plays an important role in the development of joint inflammation 37 . Moreover, M1 macrophages play a more critical role in cartilage damage in TMJOA patients than other common cell populations 38 .…”
Section: Discussionmentioning
confidence: 90%
“… 11 , 12 Meanwhile, M1 macrophage polarization plays an important role in the development of joint inflammation. 37 Moreover, M1 macrophages play a more critical role in cartilage damage in TMJOA patients than other common cell populations. 38 Inhibition of M1 macrophage polarization alleviates TMJOA.…”
Section: Discussionmentioning
confidence: 99%
“…To identify genes whose expression in CD4 + T cells is regulated by MTX, we examined comprehensive gene expression profiles of CD4 + T cells of patients with RA before and after MTX treatment, using DNA microarray analysis. We identified several differentially expressed genes (DEGs), as described previously ( 21 ). In this study, we focused on TP63 because it showed a maximum reduction in signal intensity following MTX treatment ( Figure 1A and Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Patients. Patients who fulfilled the American College of Rheumatology 1987 revised criteria for the classification of RA and received MTX therapy as a first antirheumatic drug were consecutively recruited at Chiba University Hospital and Asahi General Hospital, as described previously (21). Patients with RA who received treatment with biologic antirheumatic drugs (TNF antagonists, TCZ, or ABT) were also recruited as controls.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation